The effect of video media using audio verbal methods on learning motivation In Arabic language subjects for Student of Eighth Islamic Junior High School in Kampar/ Ta'siru Istikhdami Wasilatu Video Bistikhdami Thariqah Sam'iyah-Syafawiyah 'ala Dafi'i Ta'llum Fi Madati al-Lughah al-Arabiyah lada Talamiz fi al-Madrasah al-Mutawasshitah al-Islamiyah Hukumiyah 8 Kampar - Husnah, Qomariyatul; Moenada, Meimunah S (Al-Manar, 2023)
It was a quasi-experimental research aiming at finding out the effect of Video media with Sam’iyah Safawiyah method toward student Arabic learning motivation at State Islamic Junior High School 8 Kampar.  The formulation of the problem in this research was “what was the effect of Video media with Sam’iyah Safawiyah method toward student Arabic learning motivation at State Islamic Junior High School 8 Kampar?”.  This research was started with planning the lesson plan, implementing, observing, and distributing questionnaire.  The eighth-grade students at State Islamic Junior High School 8 Kampar in the Academic Year of 2021/2022 were the population of this research, and the samples were the eighth-grade students of classes A and B.  The subjects of this research were the eighth-grade students at State Islamic Junior High School 8 Kampar, and the object was the effect of Video media with Sam’iyah Safawiyah method toward student Arabic learning motivation at State Islamic Junior High School 8 Kampar.  Observation and questionnaire were the instruments of collecting data.  Based on data analysis, it could be concluded that there was an effect of Video media with Sam’iyah Safawiyah method toward student Arabic learning motivation at State Islamic Junior High School 8 Kampar because the score of to 11.690 was higher than tt 2.492 at 1% significant level and 2.064 at 5% significant level.  It meant that Ha was accepted and H0 was rejected.  In other words, Video media with Sam’iyah Safawiyah method affected student Arabic learning motivation at State Islamic Junior High School 8 Kampar